2022
DOI: 10.1186/s13287-022-02952-7
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of adipose-derived stem cells on soft tissue injury after radiotherapy and their value for breast reconstruction

Abstract: Background Postmastectomy radiotherapy is considered to be a necessary treatment in the therapy of breast cancer, while it will cause soft tissue damage and complications, which are closely related to the success rate and effectiveness of breast reconstruction. After radiotherapy, cutaneous tissue becomes thin and brittle, and its compliance decreases. Component fat grafting and adipose-derived stem cell therapy are considered to have great potential in treating radiation damage and improving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…Thus, although CAL was first proposed more than ten years ago, it has not been widely used in breast cancer patients until recently. As the safety of CAL in breast cancer reconstruction has gradually been confirmed, radiotherapy in breast reconstruction with CAL appears to be a diminishing relative contraindication [ 47 ]. In the present study, our results demonstrated that CAL did not increase recurrence risk; it was oncologically safe in breast cancer patients after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although CAL was first proposed more than ten years ago, it has not been widely used in breast cancer patients until recently. As the safety of CAL in breast cancer reconstruction has gradually been confirmed, radiotherapy in breast reconstruction with CAL appears to be a diminishing relative contraindication [ 47 ]. In the present study, our results demonstrated that CAL did not increase recurrence risk; it was oncologically safe in breast cancer patients after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs are partially characterized by their multilineage differentiation capacity: some common differentiation lineages for therapeutic applications include adipogenic and osteogenic cell types 94,95 . This allows for potential application of ASCs to treat a variety of conditions, including bone fractures, osteoarthritis and osteoporosis, spinal fusions, craniofacial and soft tissue defects, and cosmetic defects requiring enhanced adipogenic tissue volume 70,[96][97][98][99][100][101][102] . Overall, the multilineage differentiation capacity in ASCs is a key contributor to their therapeutic potential.…”
Section: Differentiationmentioning
confidence: 99%
“…Less research, however, focuses on complication or morbidity prediction. One study developed a protocol to investigate radiation-induced skin fibrosis resulting from breast cancer treatment, in an effort to derive an algorithm for personalized risk estimation [104] .…”
Section: Future Directionsmentioning
confidence: 99%